2013
DOI: 10.1558/cj.v23i1.49-78
|View full text |Cite
|
Sign up to set email alerts
|

Role of Students' Attitudes and Motivation in Second Language Learning in Online Language Courses

Abstract: This study investigated the role of students' motivation and attitudes in second language (L2) study within an online language course context (LOL). Students' attitudes and motivation were examined within a socioeducational framework (Gardner & MacIntyre, 1993) while learning contexts were examined based on Dörneyi's (1994) components of foreign language learning motivation. Students' learning behaviors and learning outcomes were used as predictor and criterion variables in a series of quantitative and qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
148
0
16

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(209 citation statements)
references
References 40 publications
14
148
0
16
Order By: Relevance
“…Kara (2009) argued that the positive attitudes lead to positive behavior; the participants of this study showed positive behavior to writing skill. If CLA can be considered as a new approach like technology, this study is also in line with that of Ushida (2005). Moreover, as item 6 showed, the participants did not restrict themselves to the thoughts expressed in the texts.…”
Section: Findings and Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Kara (2009) argued that the positive attitudes lead to positive behavior; the participants of this study showed positive behavior to writing skill. If CLA can be considered as a new approach like technology, this study is also in line with that of Ushida (2005). Moreover, as item 6 showed, the participants did not restrict themselves to the thoughts expressed in the texts.…”
Section: Findings and Discussionsupporting
confidence: 66%
“…Although, non-probability of its application in all contexts might be considered as a weakness but Ushida (2005) probed the motivation and attitude in relation to online learning of Spanish and French which revealed a satisfactory positive attitude. The aforementioned study beside Kern (1995), Warschauer (1996) In educational contexts of leaner-centeredness, the focal attention is chiefly on the attitude of learners; however, the teachers' view toward learning, learners and different methods play a crucial role.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, Dörnyei, Csizer, and Neineth (2006: 68ff) estimate the cardinal role of the learner's attitudes towards the learning situation and observe that it is the influence of the educational context on the individual's attitudes that influences the individual's level of motivation. Ushida (2005) investigated the role of students' attitudes and motivation in second language learning in online language courses, using Gardner and MacIntyre (1993) socio-educational framework. He sought to answer questions related to (a) patterns of motivation and attitudes toward the study of French and Spanish, (b) the relationship between attitudes and motivation on the one hand, and online learning on the other hand, (c) factors affecting students' attitudes and motivation as well as success in the study and learning of French and Spanish in an online course.…”
Section: Trends In Attitudesmentioning
confidence: 99%
“…Through factor analysis and 'split-plot' analysis of variance, they establish an intensive relationship between attitudes, integrative motivation and the anxiety of students, achievement in the language of study. Ushida (2005) summarises that this Gardnerian stream of researchers are more interested in the causal relationships among possible individual-difference variables with various achievement measures. According to Smit and Dalton (2000), this view supposes that only a positive attitude towards the target language community can lead to integrativeness, thus contributing to an overall greater motivation in language learning.…”
Section: Trends In Attitudesmentioning
confidence: 99%
See 1 more Smart Citation